A REVIEW OF MRI APPEARANCES OF LIPIODOL IN CONVENTIONAL TACE (cTACE) TREATED HEPATOCELLULAR CARCINOMAS - Rauf, Maria; Atif Iqbal Rana; Maria Rauf; Jamshaid Anwar; Haider Ali; Ahmad Ammar Afzal (Journal of Ayub Medical College Abbottabad, 2024)
Background: The global burden of patients affected by chronic liver disease (CLD) has shown a steady rise over the last few decades and is now considered the 11th most frequent cause of death globally. In addition, as the world population is facing increased obesity rates coupled with alcohol consumption, these rates are predicted to continue to rise. The Objective was to assess the appearance of Lipiodol retention upon different MRI sequences with a special focus on non-contrast sequences. Lipiodol Trans-arterial chemoembolization (TACE) has become the standard treatment for unresectable hepatocellular carcinoma (HCC) without vascular invasion. However, data regarding Lipiodol TACE imaging via MRI is limited and results are not familiar to radiologists for regular assessment of treatment response. Methods: After IRB and EC approval, we included all those patients who underwent TACE treatment with Lipiodol and chemotherapeutic agent; having both 4-6-week post-treatment CT and MRI imaging. This criterion was fulfilled by a total of 25 patients. Only lipiodol-containing areas within the lesion were noted for signal intensities on all MRI sequences and labelled as hyperintense, isointense, hypointense and mixed intensity. Data was entered and analyzed by SPSS v27. Frequencies and percentages were calculated for qualitative data. Results: The most sensitive sequence in detecting Lipiodol retention was Fat suppressed T1 imaging sequence, with low signal intensity seen on T1 weighted fat-suppressed sequences in up to 76% of lesions. While on non-fat suppressed T1 weighted images, 60% of Lipiodol retention areas appeared hyperintense. 52% of lesions showed a hypointense appearance on the T2 weighted sequence. A much more variable appearance was seen in Diffusion-weighted imaging sequences demanding cautious interpretation. MR patterns were clearer in patients having more than 50% lipiodol retention on CT and lesion size more than 2 cm. Conclusion: While MRI is deemed as a reliable and most useful imaging modality for assessing HCC’s following lipiodol TACE it requires cautious interpretation with knowledge of variable signal appearance seen on different imaging sequences.